Acesso à justiça, mediação e sistema multiportas : necessidade de cumprimento das normas vigentes sobre utilização da rede privada de serviços e remuneração dos mediadores judiciais - Marques, Hildebrando da Costa (2022)
The purpose of this dissertation is to carry out a critical analysis of the implementation and functioning, in Brazil, of the justice administration system called Multi-door Courthouse, in the light of the legal norms in force, especially: a) Resolution nº 125/2010-CNJ, which instituted the National Judicial Policy for the Adequate Treatment of Conflicts of Interest; b) the Mediation Law (Law No. 13,140/2015); and c) the Civil Procedure Code (Law No. 13.105/2015). The general objective of the research is to demonstrate the importance of the remuneration of judicial mediators and the incentive, especially on the part of the Judiciary, to the use of private mediation, by those who can pay, as measures to expand access to justice and correct implementation of the National Judiciary Policy for the Adequate Treatment of Conflicts of Interest, in compliance with current regulations. The methodological cut of the theme was established with a more specific focus on mediation, within the scope of state justice. The method used was the hypothetical-deductive, through bibliographic research, analysis of the rules in force and data collection with the courts of justice of the states and the Federal District and the National Council of Justice. Court data were obtained through visits to official websites and questionnaires sent to NUPEMECs. At the CNJ, the survey was carried out by accessing the agency's website. The problem that arises in the research is: the remuneration of judicial mediators and the incentive to use the private network for the provision of dispute resolution services are necessary measures for the correct implementation of the public policy of adequate treatment of conflicts of interest, according to the current norms, as well as for the expansion of access to justice? The dissertation was divided into three chapters, with the aim of building a theoretical basis for solving this problem. Chapter 1 addresses the updated conception of access to justice, as access to a fair legal order, presents the National Judicial Policy for the Adequate Treatment of Conflicts of Interest and demonstrates the importance of adequate treatment of conflicts for effective access to justice. Chapter 2 deepens the understanding of mediation as a self-composition method, considering that it is still an obscure topic for most of society and legal practitioners. Chapter 3 is intended to present the research carried out with the courts of justice of the states and the Federal District and the considerations aimed at solving the problem. In conclusion, the remuneration of judicial mediators and the incentive to use the private network for the provision of dispute resolution services are considered as necessary measures for the balance and correct functioning of Multiport Justice, to expand access to justice and to comply with to the current regulations. Suggestions for measures are also presented, the adoption of which is deemed to be appropriate.